Structure, Challenges and Opportunities for Development of Entrepreneurial Education in Russian Universities - Margarita Zobnina; Anatoly Korotkov; Aleksandr Rozhkov (Foresight and STI Governance, 2019)
This study explores the creation and development of entrepreneurial education tracks in the formation of a University Entrepreneurial Ecosystem (UEE) in certain Russian universities. In particular, the ways in which these tracks promote new venture launches, the commercialization of technologies, and the development of entrepreneurial mindsets and skillsets will be explored.A panel of 21 Russian Universities was used to verify the integrated UEE model using the method of co-operative inquiry. The role of entrepreneurial courses in UEEs is illustrated herein with the use of 4 cases of Russian universities.Among the key findings of this research is that the implementation of entrepreneurship education courses configures the UEE development model centered around the education course. UEE formation begins with the personal development of individuals as the course ingrains an entrepreneurial mindset and related skills in students, and attracts entrepreneurs and business angels for mentoring roles and project development activities. Next, supporting institutions like incubators and accelerators are established from scratch, or existing ones are engaged to assist further student project development. As a result, emerging elements of UEE are actively engaged around the development of student startups.Further case analysis suggests that the professors’ academic background and entrepreneurial experience, as well as the course format (e.g. elective or compulsory) are not a necessary prerequisite for the successful initiation and development of UEE, provided the course is project based and generates a stream of student startups. Professors’ skills are complemented through the ecosystem, and some cases describe successful course launches by other ecosystem actors. It is also apparent that many universities pursue entrepreneurship education through sporadic infrastructure development, or through a more detached entrepreneurship course implementation.